How Did Employee Ownership Firms Weather the Last Two Recessions? Employee Ownership, Employment Stability, and Firm Survival: 1999-2011 - Kurtulus, Fidan Ana (W.E. Upjohn Institute, 2017)
Employee ownership firms offer workers the opportunity to own a stake in the firms where they work. This affords them the ability to share in profits and have a voice in firm-related decision-making. In this comprehensive new book, Kurtulus and Kruse provide new evidence on whether employee ownership firms are better equipped to survive recessions. In particular, they focus on broad-based employee ownership, which includes ownership at all levels in the firm's hierarchy.